Kanker tydens aftrede – ‘n narratiewe benadering - Brandson, AR; Janse van Rensburg, J (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
Cancer in retirement – a narrative approach The narrative approach to therapy has attracted the attention of many therapists. Due to its post-modern philosophical roots it is however not without epistemological pitfalls for the pastoral therapist who wants to stay true to reformed pastoral principles, i.e. the use of Scripture as point of departure. This article proposes that strategies associated with narrative therapy be employed in pastoral therapy without assimilating post-modern philosophy. This hypothesis is explored against the background of the retired couple affected by cancer. As this scenario poses a real pastoral challenge, the possibilities of strategies from narrative therapy within a reformed pastoral care-model are investigated.